PEMBINAAN ANAK YANG BERKONFLIK DENGAN HUKUM DI LPKA KELAS IIB TANJUNG PATI - Tri Indah Handayani; Bob Alfiandi; Maihasni Maihasni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Children are the hope in nation building and are the key to the nation's future. Inappropriate treatment and conditions for children make children vulnerable to committing acts that violate norms and even commit crimes. Lembaga Pembinaan Khusus Anak (LPKA) is an institution whose function is to provide guidance to children so that they become good individuals again. However, in West Sumatra itself there has been an increase in the number of children who have committed repeated crimes in the last four years. The purpose of this study was to find out the programs carried out by LPKA Tanjung Pati in the framework of fostering children who commit criminal acts. This study uses a qualitative approach. Research informants were selected using a purposive sampling technique. Data collection techniques were carried out by interviews and observation. The results showed that the Lembaga Pembinaan Khusus Anak (LPKA) in providing guidance to children has two types of development programs, namely the personality program and the independence program. The coaching carried out by LPKA has been going well but it is still lacking in terms of evaluating coaching and measuring changes in children's behavior.